Identifying preliminary analysis for Developing an Integrated STEM (Science, Technology, Engineering and Mathematics) Learning Model on Chemistry Teaching in High Schools - Vera Roni Setiawan; Manihar Situmorang; Ramlan Silaban (Proceeding of International Conference on Multidisciplinary Research, 2024)
Developing a learning model at an early stage requires a needs analysis to identify the needs required by teachers, students and the applicable curriculum. This research aims find out how to implement learning models in schools in order to accommodate the learning needs of the 21st Century. The research subjects were chemistry teachers and students studying chemistry at high school level in Southwest Aceh Regency, Aceh Province. Overall, the research used the ADDIE approach, initial analysis carried out data collection using a questionnaire in the form of a questionnaire distributed via Google Form. The data obtained is the first step in further research. Based on the research results obtained, 64.3% of teachers have implemented learning that stimulates students to think at a higher level. as many as 51.7% of teachers have implemented learning models in teaching chemistry; 78.6% knew something about STEM learning, 7.1% did not know; as many as 57.1% have tried STEM learning but 50% are not satisfied with the results achieved; 85.5% acknowledged difficulties in implementing STEM in the classroom; 50% believe the STEM model influences students' thinking skills; 92.9% need a STEM integrated project learning model book. Meanwhile, of the students who obtained the results: 42.5% stated that they had difficulty understanding chemistry; 92.5% are happy if chemistry learning is connected to the real world; 92.5% stated that school textbooks were a learning resource; 55% experienced learning obstacles based on school learning resources; 90% need a learning model that connects chemical material with the real world.